Raman Spectra of High-κ Dielectric Layers Investigated with Micro-Raman Spectroscopy Comparison with Silicon Dioxide. (29th August 2013) - Borowicz, P.; Taube, A.; Rzodkiewicz, W.; Latek, M.; Gierałtowska, S.
Abstract : Three samples with dielectric layers from high- κ dielectrics, hafnium oxide, gadolinium-silicon oxide, and lanthanum-lutetium oxide on silicon substrate were studied by Raman spectroscopy. The results obtained for high- κ dielectrics were compared with spectra recorded for silicon dioxide. Raman spectra suggest the similarity of gadolinium-silicon oxide and lanthanum-lutetium oxide to the bulk nondensified silicon dioxide. The temperature treatment of hafnium oxide shows the evolution of the structure of this material. Raman spectra recorded for as-deposited hafnium oxide are similar to the results obtained for silicon dioxide layer. After thermal treatment especially at higher temperatures (600°C and above), the structure of hafnium oxide becomes similar to the bulk non-densified silicon dioxide.